Long-term functional outcome of a patient with 54% burns in the presence of inhalation burn injury - Vani Rajesh Jain; Kuldeepsinh P Atodaria; Shashank Sringapure; Jayesh M Brahmbhatt; Pradipkumar Raghuvirsinh Atodaria (Wolters Kluwer Medknow Publications, 2022)
Burns of all etiologies are among one of the leading causes of morbidity and mortality, especially those with poorer prognose. The fundamental aim of treatment is to restore the burn victim to his/her previous socioeconomic status by giving a reasonably good esthetic and functional outcome as we firmly believe that "Quality of life is as important - if not more - as life itself." This goal can be achieved by applying the basic principles of proper evaluation, adequate resuscitation, thorough planning, and apt execution of the treatment plan and has been stressed upon since time immemorial. Through this case report, we desire to show light on the other, less talked about factors, for example, psychological support, motivation for physiotherapy, rehabilitation, and occupational therapy, which play a substantial role in reinstating the patient's socioeconomic lifestyle.